Effect of climate change on nature and human health with a special focus on infectious diseases in the Mediterranean region - Dal, Tuba; Ramli, Imen; Garaizar, Javier (The Journal of Infection in Developing Countries, 2023)
Introduction: In this short review, the effect of climate change on nature and human health with a special focus on infectious diseases in the Mediterranean region is discussed. This research is a part of the Mediterranean Convention of Human Rights project, which is an organizational work on human rights issues that was established in cooperation with civil society and the national authorities of the Mediterranean Region. Methodology: Previously published data were collected by retrieving published literature from PubMed, Google Scholar, and Web of Science using “climate change”, “the Mediterranean region”, “infections in Mediterranean Region”, “infectious diseases”, “biodiversity”, and “the Mediterranean Sea” as keywords. The collected data were then evaluated and reviewed. The recommendations and guidelines were analysed by the preferred reporting items for systematic reviews and meta-analyses (PRISMA). Conclusions: The Mediterranean region presents a typical example witnessing a dramatic change in climate events and their adverse impact on biodiversity, ecosystems and public health are multiple. This negative impact is in part due to the geographical particularities, and sociocultural and geopolitical conflicts that are progressively worsening the burden of climate change. While most of these changes cannot be totally avoided, many of the health risks related to climate change could be monitored. This can be done by establishing health systems with policies to reduce and prevent the risks of infectious diseases and to recover and support the affected areas, which may identify priority and management of high-risk events.